Pengaturan Informasi Rahasia Dagang Dalam Perspektif Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Belia, Nina Rahayu (Universitas Batanghari Jambi, 2023)
The legal issues discussed in this normative research are information regulation in Law Number 8 of 1999 concerning Consumer Protection and Law Number 30 of 2000 concerning Trade Secrets and legal protection against disclosure of trade secret information in the perspective of Law Number 8 of 1999 About Consumer Protection in the future. The research method used is normative juridical research with a statute approach and a conceptual approach. The legal materials used are: primary legal materials, secondary legal materials, and tertiary legal materials. Analysis of the collected legal material is carried out by inventorying, systematizing and interpreting. The results of the study show that the regulation of information in Law Number 8 of 1999 concerning consumer protection aims to create a consumer protection system that contains elements of legal certainty and information disclosure as well as access to obtain correct, clear and honest information regarding conditions and guarantees of goods and/or or Information services and arrangements in Law Number 30 of 2000 concerning Trade Secrets provide legal protection to Trade Secret rights holders for information that is not publicly known in the field of technology and/or business, has economic value because it is useful in business activities, and is safeguarded confidentiality by the owner of the Trade Secret.